ON THE PROBLEM OF PREPARATION FOR THE PEDAGOGICAL PRACTICE (EDUCATION IN THE 21ST CENTURY, 2023)
The most important factor determining the success of the social development of any country is education, which is constantly a change connected with the scientific, social, cultural and historical development of a given country. All changes in this system depend mainly on the teacher. Therefore, the problem of teacher training is always actual. That is why, universities are faced with the question of improving the quality of teaching practice - as the most important component of the teacher training process.Pedagogical practice is the most important component in the process of preparing future teachers. The effectiveness of its implementation largely depends on the content, principles of teaching and studying the discipline «Pedagogy».The problem of organizing and conducting pedagogical practice has always been in the center of attention of Armenian, Russian scientists, teachers: N. Arutyunyan, Y. Amirdzhanyan, V. A. Popkov, A. V. Korzhuev, Y. I. Turchaninova and others. Their ideas, approaches to the solution of the problem, no doubt, are very relevant and valuable.The purpose of this article is: conducting a social survey in order to find out what difficulties students have during pedagogical practice, and to determine the ways their overcoming.To achieve this goal, we conducted a sociological survey among students of the 3rd and 4th courses after completing their teaching practice (December 2018, June 2019).Based on the analysis of the results of the sociological survey on this issue, we identified the following tasks:- development of the value-semantic orientation of the personality of the future teacher;- formation of professional and personal qualities of future teachers.It is expedient to solve the highlighted tasks during various types of training sessions (lectures, seminars, practical classes, educational practices) held within the framework of the teaching of the discipline "Pedagogy" by including an axiological component in the content of subjects, teaching, studying on a value basis, observing certain principles that keeping axiological direction. Also the use of such methods, forms of work, which most effectively contribute to the formation and development of professional and personal qualities of a teacher.The presented work is a part of a study that involves the further development, improvement of such approaches, methods, forms of work on teaching and professional education of students, which will contribute to the quality of teacher training at the university.
Keywords: Keywords: pedagogical practice, educational practice, axiological principles, pedagogical values, pedagogical activity, value-semantic sphere, professional and personal qualities.